Evidencias de validez del inventario de respuestas de afrontamiento al estrés durante el covid-19, para estudiantes universitarios de Chiclayo (Perú) - Arévalo Luna, Edmundo (2022)
This is a technological study of an instrumental type, whose objective was to obtain initial evidences of validity of a new version of the Inventory of Coping Responses to Stress, originally developed by Arévalo in 2008. First, the redefinition of the evaluated dimensions was carried out, as well as the reformulation and reduction of the quantity of items. Content validty was established through assessment by experts. The following stages of this work were carried out on university students from the city of Chiclayo (Peru), aged 18 to 25 years. Lingüístic adaptation was assessed in a first group of 20 students. The analysis of the internal structure and reliability was carried out in 200 university students and normalization in 800 students. Aiken's V coefficient values ​​were greater than .80 for each of the items; likewise, in the item-test analysis, correlations above 0.67 were obtained. The exploratory factor analysis using principal components and varimax rotation established three factors, the loads of the items in these factors were, for direct coping, between 0.679 and 0.770; in maladaptive coping, between .662 and .867 and in defensive coping, between 0.614 and 0.790. Reliability through the split-half method and Cronbach's alpha, reported values ​​above 0.80 in each of the factors. These results indicate adequate psychometric properties. Finally, we elaborated normative data for the whole sample, because no significant differences were found between the scores of men and women.